Guideline of "disciplinary incentives" (second half of the XIX century) - Tkachenko O.G (Kharkov National Pedagogical University, 2011)
Based on analysis of historical and educational literature, archival documents were analyzed and summarized the value of legal documents (circular orders, orders of the Ministry of Education, reports, and reports of various departments of education, instructions, rules, etc.) in stimulating teaching and learning of secondary school pupils. The article outlines the features of the application of measures to promote the official agencies, which have been associated with the solution of disciplinary problems. After analyzing legal documents revealed that the investigated period there was a wide range of promotional and punishing agents